Relationship between nutrition literacy and stress towards eating behaviour among IIUM students - Mohd Zafrullah, Nurul Najah Azzahra; Ibrahim, Muhamad Ariff; Saad, Nurulwahida; Waisulqrnai, Siti Adibah; Mohd Nazori, Mohd Nazir (International Islamic University Malaysia, 2024)
Background: The rising prevalence of stress and its influence on eating behaviours among university students is becoming a significant concern, especially in regard to nutrition literacy. This study examined the relationship between nutrition literacy, stress, and eating behaviour among students enrolled at the International Islamic University Malaysia (IIUM). Methods: This study used a cross sectional design and a convenience random sampling, to obtain a total sample of 384 students. A combination of questionnaires including socio- demographic questions, the Short Nutrition Literacy (S-NutLit), the Perceived Stress Scale (PSS), and the Dutch Eating Behavior Questionnaire (DEBQ), was given to respondents. Results: The study revealed a majority of students scoring a high nutrition literacy level for functional and critical, 86.7% and 79.4% respectively. There was a significant association between critical nutrition literacy and restrained eating behaviour (r=0.123, p <0.01). The stress level reported also was in moderate level which was only 70.6%. In addition, there was a significant association between stress and emotional eating behavior (r=0.142, p <0.01). The result from regression analysis showed that stress and critical nutrition literacy were significant predictors of restrained and emotional eating behaviour. Conclusion: Hence, these findings highlight the potential for enhancing students’ awareness of a healthy lifestyle by addressing the relationship between nutrition literacy and stress. Thus, it can serve as a guide to provide a good intervention in managing stress and increasing nutrition literacy level among university students.